Baseline characterization of major Iberian vegetation types based on the NDVI dynamics - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José (Plant Ecology, 2008)
We present an approach to derive baseline conditions for the radiation intercepted by vegetation in the largest remaining patches of homogeneous vegetation of the Iberian Peninsula. These baseline conditions can serve as a reference to assess environmental changes. We also characterized the major vegetation types of the Peninsula in the functional space deﬁned by the NDVI dynamics and analyzed the climatic controls of NDVI dynamics. We analysed the attributes of the NDVI seasonal dynamics: annual mean (NDVI-I), relative range (RREL), NDVI maximum and minimum values (MAX and MIN), months of MAX and MIN (MMAX and MMIN), and their inter-annual variabilities (1982–1999). We selected as reference sites only homogeneous pixels occupied by natural vegetation. We described their relationship with climatic variables using regression models. NDVI-I and RREL captured most of the variability of the NDVI annual proﬁle. Eurosiberian vegetation types were more productive, with winter minima and summer maxima. Mediterranean vegetation had summer minima and maxima distributed from autumn to spring. Interannual differences (higher in the Mediterranean) were low for NDVI-I and MAX and high for RREL and MIN. Precipitation was the main driver of NDVI-I for the Mediterranean pixels while temperature constrained it in the Eurosiberian ones. Seasonality (RREL) was associated with winter temperatures in Eurosiberian areas and with summer drought in Mediterranean ones. The Iberian vegetation types mainly differed in terms of total production and seasonality. Such differences were related to mean and inter-annual variation in precipitation and temperature associated with the Eurosiberian and Mediterranean climate zones. The NDVI dynamics allowed us to identify a functional signature for each vegetation type which captures differences that go beyond their range of climatic factors. Our baseline descriptions, based on a common approach to characterize vegetation functioning, are proposed as reference situations to evaluate the impact of environmental changes on the remaining large patches of single major natural and seminatural vegetation types.
Keywords: AVHRR/NOAA; ecosystem functioning; iberian peninsula; Normalized Difference Vegetation Index (NDVI); Regional analysis; Remote sensing

Baseline characterization of major Iberian vegetation types based on the NDVI dynamics (Plant Ecology, 2008)
We present an approach to derive baseline conditions for the radiation intercepted by vegetation in the largest remaining patches of homogeneous vegetation of the Iberian Peninsula. These baseline conditions can serve as a reference to assess environmental changes. We also characterized the major vegetation types of the Peninsula in the functional space deﬁned by the NDVI dynamics and analyzed the climatic controls of NDVI dynamics. We analysed the attributes of the NDVI seasonal dynamics: annual mean (NDVI-I), relative range (RREL), NDVI maximum and minimum values (MAX and MIN), months of MAX and MIN (MMAX and MMIN), and their inter-annual variabilities (1982–1999). We selected as reference sites only homogeneous pixels occupied by natural vegetation. We described their relationship with climatic variables using regression models. NDVI-I and RREL captured most of the variability of the NDVI annual proﬁle. Eurosiberian vegetation types were more productive, with winter minima and summer maxima. Mediterranean vegetation had summer minima and maxima distributed from autumn to spring. Interannual differences (higher in the Mediterranean) were low for NDVI-I and MAX and high for RREL and MIN. Precipitation was the main driver of NDVI-I for the Mediterranean pixels while temperature constrained it in the Eurosiberian ones. Seasonality (RREL) was associated with winter temperatures in Eurosiberian areas and with summer drought in Mediterranean ones. The Iberian vegetation types mainly differed in terms of total production and seasonality. Such differences were related to mean and inter-annual variation in precipitation and temperature associated with the Eurosiberian and Mediterranean climate zones. The NDVI dynamics allowed us to identify a functional signature for each vegetation type which captures differences that go beyond their range of climatic factors. Our baseline descriptions, based on a common approach to characterize vegetation functioning, are proposed as reference situations to evaluate the impact of environmental changes on the remaining large patches of single major natural and seminatural vegetation types.

Trends in the surface vegetation dynamics of the national parks of Spain as observed by satellite sensors - Alcaraz-Segura, Domingo; Cabello, Javier; Paruelo, José M.; Delibes, Miguel (Applied Vegetation Science, 2008)
Questions: What are the current dynamics, as observed by synoptic sensors, of surface vegetation in Spanish protected areas? Are these areas and their vegetation types uniformly affected by the increase in vegetation greenness detected throughout Europe? Location: Iberian National Parks of Spain. Methods: We used the normalized difference vegetation index (NDVI) from global inventory modeling and mapping studies (GIMMS) advanced very high resolution radiometer (AVHRR) dataset to monitor surface vegetation. NDVI is a surrogate for the photosynthetically active radiation absorbed by vegetation (fAPAR). This functional attribute has a short-time response to disturbances, is connected to ecosystem services and can be monitored through remote sensing. First, we provide a baseline description of the NDVI dynamics in the parks and analysed its temporal trends (1981-2003). Then, we evaluated the relationships of the seasonal dynamics and interannual trends with the climate conditions, vegetation types and conservation histories of the parks. Results: The parks showed two patterns of NDVI dynamics corresponding to Mediterranean and Eurosiberian regions. Most parks showed areas with positive NDVI trends that tended to have higher proportions of Mediterranean coniferous and mixed forests, oro-Mediterranean scrublands, heathlands, maquis and garrigues. Negative trends were scarce and associated with marshes and Alpine coniferous forests. The lack of a common response in all parks was related to their different environmental conditions, management, and conservation histories. Conclusions: National parks are changing in the short term but not uniformly. This study represents a basis for the incorporation of functional attributes of ecosystems in the management and monitoring of protected areas in the face of global change.
Keywords: Global environmental change; monitoring; National Park conservation; NDVI; Remote sensing.

Trends in the surface vegetation dynamics of the national parks of Spain as observed by satellite sensors (Applied Vegetation Science, 2008)
Questions: What are the current dynamics, as observed by synoptic sensors, of surface vegetation in Spanish protected areas? Are these areas and their vegetation types uniformly affected by the increase in vegetation greenness detected throughout Europe? Location: Iberian National Parks of Spain. Methods: We used the normalized difference vegetation index (NDVI) from global inventory modeling and mapping studies (GIMMS) advanced very high resolution radiometer (AVHRR) dataset to monitor surface vegetation. NDVI is a surrogate for the photosynthetically active radiation absorbed by vegetation (fAPAR). This functional attribute has a short-time response to disturbances, is connected to ecosystem services and can be monitored through remote sensing. First, we provide a baseline description of the NDVI dynamics in the parks and analysed its temporal trends (1981-2003). Then, we evaluated the relationships of the seasonal dynamics and interannual trends with the climate conditions, vegetation types and conservation histories of the parks. Results: The parks showed two patterns of NDVI dynamics corresponding to Mediterranean and Eurosiberian regions. Most parks showed areas with positive NDVI trends that tended to have higher proportions of Mediterranean coniferous and mixed forests, oro-Mediterranean scrublands, heathlands, maquis and garrigues. Negative trends were scarce and associated with marshes and Alpine coniferous forests. The lack of a common response in all parks was related to their different environmental conditions, management, and conservation histories. Conclusions: National parks are changing in the short term but not uniformly. This study represents a basis for the incorporation of functional attributes of ecosystems in the management and monitoring of protected areas in the face of global change.